Pengungkapan Perusahaan: Finansial atau Non-Finansial Studi Kasus pada Emiten Syariah di Indonesia - Syarief, Mochamad Edman (Jurnal ASET (Akuntansi Riset), 2020)
This study investigates how investors' perceptions of disclosures made by companies. The disclosure referred to non-financial exposures represented by corporate governance disclosures (GCGs) and financial disclosures denoted by ROA and ROE. The stock price is a proxy for investor perceptions. Furthermore, this study also tries to see whether the regulations issued by the Financial Services Authority have an economic impact on the company that implements these rules. This research using WarpPLS as a tool to find out the influence of GCGs on ROA and ROE, and on Share Prices, using path analysis before and after 2014. The results of the study state that GCGs has a positive and significant effect on ROA before and after 2014. GCGs does not affect ROE before 2014, but it had a significant positive impact on ROE after 2014. GCGs did not affect stock prices before and after 2014. ROA had a significant effect on stock prices before 2014, did not affect stock prices after 2014. ROE does not influence the Share Price before and after 2014. The conclusion is that the investors on sharia stock still acknowledge that financial information is more decisive for buying shares of sharia stocks compared to non-financial information, and non-financial disclosures made by the company, adding to the burden of the company.Â The rules issued by OJK relating to disclosure of corporate governance do not appear to have had an economic effect on Islamic issuers in Indonesia.